Утворення та діяльність кафедри канонічного права на юридичному факультеті Львівського університету у 1784-1864 рр. - Кахнич, В.; Kakhnych, V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена утворенню та діяльності кафедри канонічного права на юридичному факультеті Львівського університету з 1784 року. Досліджено процес діяльності кафедри на різних етапах становлення юридичного факультету Львівського університету, його професорсько-викладацький склад. Проаналізовано значення багатьох завідувачів кафедри канонічного права та їх внесок у розвиток та діяльність кафедри. The article is devoted to the formation and activities of the Department of Canon Law at the Faculty of Lviv University in 1784. Austrian Emperor Joseph II special diploma in October 1784 restored the Lviv University. The grand opening of the university, known as Emperor Joseph Lviv University, held November 16, 1784. In addition to refurbished former philosophical and theological faculties in 1784 was created the legal and medical faculties. Department of canon law existed in the structure of the Faculty of Law in 1784. It was headed by such prominent scholars as: Jan Ambros (1784-1806), Franz Zommaruha (1806-1809) and Jan Dobzhansky (1809-1810). In 1810, this department was transformed into a chair of canon and Roman law, which in 1810-1821 he headed Bernard Baron, in the years 1821-1842 - Anthony Haymberher, and from 1842 - Francis Cotter. In 1856 the Department of canon and Roman law Roman law department highlighted (manager: 1856-1857 years - J. Shvah, seams with 1857 - Jehoshaphat Zelonatskyy). Therefore, in 1858, Department of canon and Roman law again called «Department of canon law». Then it was headed by Eugen Mohr.
Fоrmation and Activities of the Department of the Canon Law at the Faculty of Law of Lviv University in 1784-1864
Keywords: Львівський університет; юридичний факультет; кафедра канонічного права; професорсько-викладацький склад; Lviv University; Faculty of Law; Department of canon law